Effective Formation Tracking of Quadrotors with Intelligent Disturbance Observer-Based Control - Noor Hanis Izzuddin Mat Lazim; Liyana Ramli; Abdul Rashid Husain; Zaharuddin Mohamed; Mohd Ariffanan Mohd Basri; Nurul Adilla Mohd Subha (Springer Nature, 2024)
Indexed by WOS/Scopus